2016
DOI: 10.2217/nnm-2016-0293
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Selective Sonosensitizing Efficacy of Ultrasound-Based Anticancer Treatment By Targeted Gold Nanoparticles

Abstract: The combined use of targeting capacity and the ultrasound sensitizing effect, make FA-PEG-GNP promising candidates for the site-specific cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 70 publications
1
49
0
1
Order By: Relevance
“…In this case, the NPs acted as sources of nucleation sites, enhancing the inertial cavitation rate in biological environment, and the minor resistance of cancer cells to physical stress is exploited with respect to healthy ones [105]. A recent study [106] on gold NPs, functionalized with PEG and folic acid and activated with ultrasound, showed a promising reduction in cancer cells growth, accompanied by a significant generation of ROS species. Sazgarnia et al [107] also found that the combination of gold NPs, ultrasound and intense pulsed light was a good strategy to further improve the therapeutic effect on tumors.…”
Section: Nps Used In the Sonodynamic Therapymentioning
confidence: 99%
“…In this case, the NPs acted as sources of nucleation sites, enhancing the inertial cavitation rate in biological environment, and the minor resistance of cancer cells to physical stress is exploited with respect to healthy ones [105]. A recent study [106] on gold NPs, functionalized with PEG and folic acid and activated with ultrasound, showed a promising reduction in cancer cells growth, accompanied by a significant generation of ROS species. Sazgarnia et al [107] also found that the combination of gold NPs, ultrasound and intense pulsed light was a good strategy to further improve the therapeutic effect on tumors.…”
Section: Nps Used In the Sonodynamic Therapymentioning
confidence: 99%
“…Polymer-metal hybrid nanoparticles offer many advantages for diagnosis and therapy, owing to the possibility to endow these materials with multiple functionalities for detecting disease, releasing therapeutic agents or treat the pathology by enhancing externally applied physical stimuli. [1][2][3][4][5][6] However, the clinical applications of nanoparticles in general have been limited by complex and unpredictable pharmacokinetics and targeting. [7][8][9][10] In order to achieve maximal clinical response in vivo any diagnostic or therapeutic agent needs to accumulate at the target tissue and gain access to disease relevant cells and appropriate intracellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the various types of materials that can be loaded into the vesicles with the techniques described above, we can assert that NPs can be finely tuned for a wide number of applications through a strict control of physical and chemical parameters [112]. However, when administered into the body, they could face some problems such as opsonization and/or aggregation [113,114].…”
Section: Loading Nanotechnological Modification Into Evsmentioning
confidence: 99%